Liability for negligent conduct in a heterogeneous society with reference to South African and German criminal law - Grant, Evadne (Institute of Criminology, 2023)
The study of criminal law by lawyers has traditionally been confined to a consideration of general principles of criminal law and of specific crimes, the material or substantive criminal law.